An Attempt to Elucidate the Relationship Between Biological and Cultural Factors in Philosophy - Ryszard F. Sadowski (Studia Philosophiae Christianae)
Today, we observe disturbing phenomena accompanying technical civilization’s dynamic development. While noticing the great benefits and achievements of civilizational development, we also experience the challenges and difficulties that humanity and our planet face today. Konrad Lorenz with his “layered” concept of man is the key to analyzing civilizational changes and, consequently, identifying threats and indicating possible solutions. Lorenz’s concept allows him to identify eight “deadly sins” of civilized humanity, which challenge human civilization and even threaten humans’ very humanity. Three of Lorenz’s eight “sins” seem particularly important for the practice of philosophy: (1) overpopulation, (2) man’s race against himself, and (3) indoctrinability. As a result of the significant acceleration in the development of our civilization that we have observed since the Neolithic Revolution, we see both obstacles and catalysts to the development and practice of philosophy – this specifically human ability. While in the initial period of civilizational development the consequences of the Neolithic revolution contributed to the development of philosophy, now they make it challenging to practice philosophy. Lorenz’s “sins” contribute to human loneliness, neurotic hyperactivity and to the unification of culture. All these factors constitute obstacles to philosophy. The answer to these threats is to create communities where people can establish deep interpersonal relationships and share their life experiences. Another helpful factor is contact with nature, which helps slow the pace of life and escape from the overwhelming noise that prevents reflection on the meaning of human existence.